Performance analysis of mixed‐ADC receiver multiuser massive MIMO relaying system under imperfect CSI. Issue 20 (1st December 2019) - Ding, Qingfeng; Wei, Min; Liu, Mengxia; Lian, Yichong
Abstract : In this paper, the authors investigate a multiuser massive multi‐input‐multi‐output (MIMO) relay system with mixed analog‐todigitalconverter (ADC) architecture. It is assumed that the channel state information (CSI) is imperfect between the relay and the user. Sum Spectral efficiency (SE) and Energy efficiency (EE) with the maximum‐ratio combining (MRC) detector are derived. In addition, the authors have studied the trade‐off between achievable Spectral efficiency and energy efficiency. it is revealed that the trade‐off between the sum SE and EE with respect to key system parameters, including number of BS antennas, user transmit power, the power of the CSI error, and the quantization bits. Finally, numerical results show that the mixed‐ADC structure can obtain a better energy‐rate trade‐off than low‐precision ADC structure.